2014
DOI: 10.1055/s-0033-1363258
|View full text |Cite
|
Sign up to set email alerts
|

Treatments for Acute Bipolar Depression: Meta-analyses of Placebo-controlled, Monotherapy Trials of Anticonvulsants, Lithium and Antipsychotics

Abstract: Background: Optimal treatments for bipolar depression, and the relative value of specific drugs for that purpose, remain uncertain, including agents other than antidepressants. Methods: We searched for reports of placebo-controlled, monotherapy trials of mood-stabilizing anticonvulsants, second-generation antipsychotics, or lithium for acute major depressive episodes in patients diagnosed with type I or II bipolar disorder and applied random-effects meta-analysis to evaluate their efficacy, comparing outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
71
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(87 citation statements)
references
References 60 publications
5
71
0
Order By: Relevance
“…Quetiapine (level 1),241, 242, 243 lithium (level 2),244, 245, 246 lamotrigine (level 2)242, 247, 248 and lurasidone (level 2)249 are all recommended as first‐line treatment options with evidence for efficacy as monotherapy.…”
Section: Acute Management Of Bipolar Depressionmentioning
confidence: 99%
See 3 more Smart Citations
“…Quetiapine (level 1),241, 242, 243 lithium (level 2),244, 245, 246 lamotrigine (level 2)242, 247, 248 and lurasidone (level 2)249 are all recommended as first‐line treatment options with evidence for efficacy as monotherapy.…”
Section: Acute Management Of Bipolar Depressionmentioning
confidence: 99%
“…In patients who are inadequately responsive to first‐line agents, monotherapy with divalproex (level 2)242, 258 is included as a second‐line option.…”
Section: Acute Management Of Bipolar Depressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meta-analysis was applied to the findings from the remarkably few randomized, controlled trials (approximately 20 for all non-antidepressants) that have been reported for this condition, and virtually only for acute bipolar depression (47). Ranked by apparent efficacy, the most promising treatments were: olanzapine+fluoxetine ≥ valproate ≥ quetiapine ≥ lurasidone ≥ olanzapine alone, whereas carbamazepine, lithium, lamotrigine, ziprasidone, and aripiprazole had lesser outcomes and were not statistically effective.…”
mentioning
confidence: 99%